The towering inferno - Robinson, Frank M. 1926-2014; Silliphant, Stirling 1918-1996; Williams, John 1932-; Stern, Richard Martin 1915-2001 (Warner Home Video, 2008)
Due to substandard materials and workmanship, one of the world's tallest skyscrapers catches fire during its gala opening, trapping a large crowd of society guests.
Orig.: USA, 1974
Keywords: Actionfilm; Film; Hochhaus; Katastrophenfilm; Verfilmung; Skyscrapers / California / San Francisco / Drama; Fire extinction / California / San Francisco / Drama; Parties / California / San Francisco / Drama; Architects / California / San Francisco / Drama; Electric contracting / California / San Francisco / Drama; Architects; Electric contracting; Fire extinction; Parties; Skyscrapers; California / San Francisco; Action and adventure films; Disaster films; Drama; Feature films; Film adaptations; DVD-Video